2014
DOI: 10.1177/1063426613519820
|View full text |Cite
|
Sign up to set email alerts
|

Use of Coaching and Behavior Support Planning for Students With Disruptive Behavior Within a Universal Classroom Management Program

Abstract: Even with the use of effective universal classroom management practices, some students will need additional behavioral supports. However, to translate implementation of new strategies into the classroom, professional development programs need to be adaptive to the complexities teachers face in providing instruction and managing classroom behaviors among diverse learners. Teachers also need support to successfully implement universal practices as well as to develop and enact plans for supporting students with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 26 publications
2
61
1
6
Order By: Relevance
“…First, prior literature emphasizes that teacher-focused PD needs to adopt more 'hands on' and 'in class' training for mental health (Reinke et al, 2014). The PD plus coaching model used in this study reduced the need to remove teachers from their classrooms to attend additional training sessions and allowed teachers to 'learn by example' rather than trying to interpret, learn and role play the new strategies during the didactic training.…”
Section: Discussionmentioning
confidence: 99%
“…First, prior literature emphasizes that teacher-focused PD needs to adopt more 'hands on' and 'in class' training for mental health (Reinke et al, 2014). The PD plus coaching model used in this study reduced the need to remove teachers from their classrooms to attend additional training sessions and allowed teachers to 'learn by example' rather than trying to interpret, learn and role play the new strategies during the didactic training.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have focused on the effectiveness of IY TCM among both clinical populations (Webster-Stratton, Reid, & Hammond, 2004) and mainstream classrooms (Baker-Henningham et al, 2012;Hutchings et al, 2013;Reinke et al, 2014), no study has yet focused on the appropriateness of the IY TCM Programme for children identified with SEN. A limitation of this study is that its qualitative design does not allow for any conclusions to be made about the effectiveness of the IY TCM Programme for children identified with SEN in mainstream schools. While the relatively small sample size might raise questions about data saturation, empirical research suggests that when the aim is to describe common behaviours/beliefs, a sample of 12 is sufficient for saturation, and overarching themes emerge from samples as small as six (Guest, Bunce, & Johnson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As an important factor in both academic and social-emotional-behavioral development, classroom management has been widely investigated (e.g., Coetzee, Niekerk, & Wydeman, 2008;Marzano, Gaddy, Foseid, Foseid, & Marzano, 2005), and many classroom management programs have been developed and investigated for their effectiveness (Poduska & Kurki, 2014;Reinke et al, 2014). Classroom management is also important as a supportive strategy, a relationship perhaps best understood by the fact that classroom management and teachers' supportive behaviors are two complementary concepts (Kylie & Rogien, 2015).…”
Section: Discussionmentioning
confidence: 99%